Social Equity in Urban Infrastructure Planning - Sugiyantoro, . (Journal of Regional and City Planning, 2001)
Social equity in urban infrastructure planning is important, especially where the infrastructure investment is high, and charging systems are applied: this will lead some people could not afford a fair delivery of services. The role of the planners is important to secure infrastructure delivery for the poor within the adopted and applied planning system in a respective country to anticipate the trend of privatization in production and delivery of infrastructure and services.